2021
DOI: 10.3390/vaccines9121444
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vaccination on the Sense of Security, the Anxiety of COVID-19 and Quality of Life among Polish. A Nationwide Online Survey in Poland

Abstract: The pandemic state has a destructive effect on the human psyche and induces fear for one’s own health. By reducing the risk of severe COVID-19, vaccination may indirectly improve the mental state. This study aims to assess the effects of vaccination on respondents’ mental well-being, their attitudes towards adherence to government recommendations limiting viral transmission, and to identify factors that may influence the decision to get vaccinated. The survey took the form of the authors’ own, fully voluntary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 40 publications
6
37
2
Order By: Relevance
“…Our analysis determined that a lower level of education and a lower income were predictors of vaccination reluctance [22,23], which was similar to prior results from a study conducted in France [24]. This association contrasts with prior research on vaccination that indicated that more educated and wealthy individuals expressed more anxiety about vaccine safety [25,26].…”
Section: Discussionsupporting
confidence: 68%
“…Our analysis determined that a lower level of education and a lower income were predictors of vaccination reluctance [22,23], which was similar to prior results from a study conducted in France [24]. This association contrasts with prior research on vaccination that indicated that more educated and wealthy individuals expressed more anxiety about vaccine safety [25,26].…”
Section: Discussionsupporting
confidence: 68%
“…The current findings provide evidence that vaccination with a COVID-19 vaccine reduced the psychological needs of cancer patients during the Shanghai lockdown, but the relevant evidence is still mixed. Like the current study, a Polish study of 1,696 participants reported that COVID-19 vaccination reduced the level of anxiety about being infected and anxiety due to COVID-19 (30). Another study in the United States found that vaccinated participants were 15% less likely to be anxious (adjusted odds ratio [AOR]: 0.85, 95% CI: 0.83-0.90) and 17% less likely to be depressed (AOR: 0.83, 95% CI: 0.79-0.85) compared to those who were not vaccinated (31).…”
Section: Resultssupporting
confidence: 54%
“…The current factor that reduces pandemic fear is the ability to receive a vaccination [ 52 ]. An interesting, previously unexplored topic was the attitude of recreationists toward COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%